Effect of dietary supplimentation of azolla (azolla pinnata) on production performance in Japanese quail (Coturnix coturnix japonica) - Raseena Karim (Department of Poultry Science,College of Veterinary and Animal Science, 2006)
The utility of dried Azolla in the production performance of Japanese quails were evaluated using one hundred and ninety two layer quails for a period of 20 weeks. They were randomly allotted to four treatment groups with four replicates of 12 quails each. Quail layer ration containing 22 per cent crude protein, 2650 kcal per kg metabolisable energy, 3.0 per cent calcium and 0.45 per cent phosphorus formed the basal diet (T1). Dried Azolla was included in the basal diet at levels of 1.5, 3.0 and 4.5 per cent to form the treatments T2, T3 and T4, respectively. All the rations were made isocaloric and isonitrogenous. Data collection was done for five periods of 28 days each from 7 to 26 weeks of age. At the end of the trial, blood was collected from two birds per replicate and was utilised for serum profile studies. The body weight at 6 and 26 weeks of age and the body weight gain during experimental period did not differ significantly between dietary treatments. Age at sexual maturity, 10 and 50 per cent production were not influenced by inclusion of Azolla in quail diets. The quails fed with Azolla recorded numerically higher feed intake than control group. The cumulative feed conversion ratio was numerically higher in Azolla fed groups. Eventhough the cumulative mean quail housed and quail day egg number and per cent production were statistically comparable among the dietary groups, the groups T2 and T4 performed better than the control (T1). The cumulative mean egg weight from 7 to 26 weeks of age was highest for T3 followed by T2, T4 and T1. Cumulative egg weight was significantly (P<0.05) higher in 3.0 per cent Azolla fed group. The statistical analysis of the overall mean values of egg quality traits revealed no significant difference between dietary groups with the exception in yolk index. The cumulative mean yolk index was significantly (P<0.01) lower in Azolla fed birds. The mean yolk carotenoids level was significantly higher (P<0.01) with Azolla supplemented groups in all individual periods and for the whole experimental period taken together. Mean per cent giblet and ovary and oviduct weight were numerically higher for Azolla supplemented groups. The group fed with 1.5 per cent Azolla (T2) recorded numerically higher dressed yield (83.73 %) and the group fed with 4.5 per cent Azolla (T4) recorded numerically higher ready-to-cook-yield (60.07 %). While the statistical analysis of the mean values of these traits showed no significant difference. Mean serum total cholesterol was significantly (P<0.01) lower in 3.0 and 4.5 per cent Azolla fed groups compared to control. Serum total protein, creatinine, and uric acid were not influenced due to Azolla inclusion. Livability was comparatively better in Azolla fed birds. The cost of feed per egg was lowest in T4 followed by T1, T2 and T3. Overall evaluation of the results of the study indicated that incorporation of the dried Azolla at 4.5 per cent level in quail layer ration was beneficial.